Related Factors with Depression in Patients Interesting Yourself at Home mental illness Dr. Suparto Hardjohoesodo Kendari - Harun, Basmalah (ScieClouds Publishing, 2023)
Depression is one of the form disturbance psychology in nature feeling (affective/mood disorder) , which is marked with melancholy , listlessness , nothingness excitement life , feeling No useful , break up hope and so on . Interesting self is something circumstances experiencing patients _ no ability For stage connection with other people or with environment surrounding in a way natural and alive in imaginary myself who doesn't realistic . Objective study This know related factors _ with depression in patients interesting yourself at home Mental Illness Dr. Suparto Hardjohoesodo Kendari. Method study This is descriptive analytic whereas approach used _ is approach cross-sectional. Population in study This is all over patient disturbance soul at RSJ Dr. Suparto Hardjohoesodo Kendari numbered 148 patients . Retrieval technique sample is random sampling. Variable independently measured _ is type gender , age , occupation and education , meanwhile variable dependent is interesting self . Data collection using questionnaire . Data is presented in form tested tables and narratives _ statistics chi-square with level meaning p = 0.05 for know connection between independent and dependent . Research result based on chi-square show consecutive based on type gender , age , occupation and education as following mark p = 0.012, p = 0.034, p = 0.013 p = 0.024 meaning There is connection between type gender , age , occupation and education with depression in patients interesting self . Deep conclusion study This is There is connection between type gender , age , occupation and education with depression in patients interesting yourself at home Mental Illness Dr. Suparto Hardjohoesodo Kendari. Deep advice study This is to always notice circumstances patient and provide care professional nursing _ in effort healing patient depressing and interesting self.